Pengaruh Kesejahteraan Dan Semangat Kerja Pada Karyawan Pt Karya Asri Mandiri - Topik Hidayat; Sungkono Sungkono (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
PT Karya Asri Mandiri provides employee welfare in increasing employee morale. The welfare provided includes pensions, bonuses, holiday allowances, office clothing, facilities and services. To achieve common goals where the interests of the company can be achieved and the needs of employees can be met. This study aims to explore the influence of work welfare and morale on the employees of PT Karya Asri Mandiri. This study used descriptive qualitative methods, data collection techniques were carried out qualitative research to produce and process descriptive data, such as interview transcripts and observations. It can be concluded that PT Karya Asri Mandir has a pretty good social program for some of the services offered, such as travel bonuses and bonuses. money, can increase the motivation and well-being of employees. However, there are also conditions that must be met, such as one customer per month to receive a payday. This can cause pressure and stress for employees, so it is necessary to think about how the company can help employees achieve these goals.